The board and strategy: Venture capital and high technology - Rosenstein, Joseph (Journal of Business Venturing, 1988)
In the area of strategy formulation, the part played by the board of directors in high technology firms operating with funds provided by venture capital organizations has not been investigated before. This exploratory study, although based on a limited sample, looks at some of the fundamental issues and contrasts the involvement of the board in firms of this kind with very limited involvement of the board in small conventional firms and in large publicly-held corporations. The relative power of management and the board of directors is of great importance. In contrast with the small conventional firm and the large corporation, in both of which the Chief Executive Officer is usually in firm control of the board and generally does not look to the board for active involvement in strategy formulation, the high-technology firms funded by venture capital organizations are characterized by a board of directors that has high power relative to management. This power can be understood not only in terms of the “power of the purse” (high concentration of the ownership in hands external to management), but also in terms of the expertise of the venture capitalists and their access to important networks. The business plan which is a key element in obtaining initial funding is in effect a statement of strategy that is carefully scrutinized by the venture capitalists, some of whom will assume positions on the board of directors. The board is similarly involved in the revisions of business plans in conjunction with later rounds of funding. The study found that the board is typically small, with outsiders rather than management in control; further, at least some of the outside members were found to have a high degree of expertise and a close working relationship with management. Board meetings are frequent and deal actively with key issues and with the review of how the strategy is working and what changes in strategy may be required. Reviews of the business plan when a new round of funding is required or when major new product or marketing decisions are needed are examples of likely occasions for involvement of the board in strategy revisions. Further research should center on identifying the conditions under which board involvement can play a constructive role in the strategy process of these high technology companies. Some pertinent variables are suggested. The next step in research should be more structured and quantitative and should use a geographically dispersed sample, but field interviews will be of continuing value as a complement. For firms funded by venture capital organizations, the board of directors is a significant interface between the venture capitalists and the internal management group. The working relationship between inside and outside directors in this arena, in strategy formulation and in other major business decisions, is a matter of considerable practical importance.